Investigation of TiO2-added refractory brick properties from calcined magnesite raw material - Kalpakli, Y. K. (CONSULTANTS BUREAU/SPRINGER, 2008)
This paper is the second part of a study on recycling magnesite and chromite ore (in the 0-10(-3) m fraction) powder, which remains as a production process waste. In this work, 90% magnesite-10% chromite composition was used as a brick composition. Compaction pressure, sintering temperature, ratio of TiO2 addition, and influence of bonding type on refractory properties were examined. In refractory brick production, one of the most important parameters that affects the properties of the product is the particle size distribution of the blend. Experiments show that using a magnesite particle size of -10(-3) m and a chromite particle size of -63x10(-6) m affects the properties of the product in a positive way. Experiment blends with the particle sizes selected above were used. Magnesite ore was used in experiments after calcination at 1200A degrees C for four hours. In the experiments we mention, MgCl2 and MgSO4 solutions were used as a bonding agent, as a result of which a 6% bonding ratio of MgCl2 and MgSO4 solutions was determined as optimum. The effect of compacting pressure on the refractory properties was studied, and the optimum compacting pressure was determined as 180 MPa. For bricks prepared using calcined magnesite, the optimum sintering temperature was found to be 1750A degrees C. The positive effect of TiO2 addition on the magnesite chrome refractory brick structure has been reported in the literature. Thus, 1, 3, 5, and 7 wt.% TiO2 ratios were used in the blend, and the refractory properties were positively affected by the 3% TiO2 addition. Taking the result of the MgCl2 and MgSO4 bonding solution into consideration, it is clear that the refractory properties of brick can be improved by using a mixture of MgCl2 and MgSO4 bonding solutions. In light of the above concept, bonding mixtures with 1:3, 1:5, and 1:10 ratios were prepared, and these bonding mixtures were studies as a bonding material. The experimental results show that the cold crushing strength (CCS) and volume density of bricks increase, whereas the porosity decreases when a 1:5 ratio of MgCl2 and MgSO4 in the bonding mixture and 3% TiO2 addition were used. Microstructural study of the produced bricks was done using scanning electron microscope (SEM). In addition to this, the phases forming the structure of brick were examined via x-ray diagrams of the material. In bricks where a mixture of a 1:5 MgCl2: MgSO4 bonding solution was used as bonding agent and 3% TiO2 was added, spinel (magnochromite (MgCr2O4)), magnesium orthotitanate (Mg2TiO4), monticellite (CaMgSiO4), and forsterite (Mg2SiO4) phases were found. The perovskite phase was not observed during the experimental study.
Keywords: Materials Science